A STUDY OF 3D PRINTING FOR COSMETIC PACKAGING ON SURFACE ROUGHNESS AND WATER ABSORPTION_ TAGUCHI APPROACH - ZAHARUDIN, AZNIFA MAHYAM; MOHD HISHAMUDIN, NURUL AMYRA; AB HAMID PAHMI, MUHAMMAD ARIF (MALAYSIAN JOURNAL OF INNOVATION IN ENGINEERING AND APPLIED SOCIAL SCIENCES (MYJIEAS), 2024)
ABSTRACT - Cosmetics possessed the potential to develop novel packaging through the utilization of 3D printing, an additive manufacturing (AM) technique that offered advantages over traditional manufacturing methods. This study aimed to optimize the 3D printing process parameters for cosmetic packaging using the Taguchi approach. A cosmetic packaging bottle using polylactic acid (PLA) filament was chosen for 3D printing prototype. The research employed an L9 orthogonal array to investigate the effects of infill density (3%, 5% and 10%), infill pattern (cross, triangle and tri-hexagon) and printing speed (30 mm/s, 50 mm/s and 100 mm/s) on surface roughness and water absorption. The optimal parameters for surface roughness were infill density of 5%, a tri-hexagon infill pattern and a printing speed of 50 mm/s. Printing speed displayed the greatest influence on reducing water absorption in the 30 printed parts. The study demonstrates the effectiveness of the Taguchi approach in optimizing 3D printing parameters for cosmetic packaging, ensuring a desirable surface finish, reduced porosity and longevity.